Use of Lumbar Puncture for First Episode of Febrile Seizure among Children 6 Months to 18 Months of Age: A Cross Sectional Study - Kayastha, Nirajana; Rai, Ganesh Kumar; Karki, Subhana (Birat Journal of Health Sciences, 2018)
Introduction: Febrile seizure accounts for the majority cases of the pediatric seizure. Fever with seizure can be either due to febrile seizure or underlying serious infection as meningitis. As seizure may be the only manifestation of meningitis it is important to rule out meningitis in children presenting with fever and seizure. Objective: The objective of this study was to determine the incidence of meningitis among children aged 6 to 18 months presenting with first episode of febrile seizure. Methodology: A prospective observational study was conducted among 94 children with first episode of febrile seizure presenting to the emergency and observation wards of Kanti Childrens' Hospital and subjected to lumbar puncture (LP) as per the American Academy of Pediatrics (AAP) recommendations. The proportion of children with meningitis and no meningitis among the study population was determined, clinical characteristics were compared among these groups and the incidence of meningitis in simple febrile seizure and complex febrile seizure was calculated. The collected data was analysed using SPSS. Results: Twenty (21.3%) cases were diagnosed with meningitis among 94 children enrolled in our study. Meningitis was detected in 38.1% of the cases of complex febrile seizure and 7.7% of cases of simple febrile seizure. In the age group 6 to 12 months, 11 (17.4%) had meningitis while in 12 to 18 months of age, 9 (29%) were detected with meningitis. Meningitis was 7.38 times more likely in cases presenting with complex febrile seizure than simple febrile seizure (OR=7.58; 95% CI 2.24-24.4; p<0.001). Regarding the clinical characteristics, vomiting, fever of more than 48 hours duration prior to onset of seizure, impaired consciousness and complex features of seizure were found to be significantly associated with meningitis in our study. Conclusion: The probability of meningitis among children aged 6 to 18 months presenting with first episode of febrile seizure episode is high. In febrile convulsing children less than 18 months of age, meningitis should be considered even in the absence of signs of meningeal irritation. BJHS 2018;3(2)6:399-402.